English Learning with Powtoon Animation Video - N.M.S, Megawati; I.G.A.L.P, Utami (Universitas Pendidikan Ganesha, 2020)
The use of technology media for teaching young learners was really needed. In daily teaching, teacher rarely use the technology based on media. This happened because it was quite difficult to find the media which was appropriate with the syllabus. Therefore, the aim of this research was to develop PowToon Animation Video on fifth grade students of SD N 3 Banjar Jawa. This research used Design and Development as the method with ADDIE model as the research procedures. This research answered the research questions related to the development of the product. Some steps were conducted to develop the product. In developing the product, it needed analysis, designed the blueprint, asked for expert judgments before the product was developed, evaluated and revised the product. The result of this research was categorized as the best media based on the expert judgment rubrics. So it could be said that PowToon media was effective applied in elementary school, this would directly able to enrich the existing media technology in learning English.